Initial peri- and postoperative antibiotic treatment of infected nonunions: results from 212 consecutive patients after mean follow-up of 34 months - Helbig, Lars; Bechberger, Maren; Aldeeri, Riyadh; Ivanova, Adriana; Haubruck, Patrick; Miska, Matthias; Schmidmaier, Gerhard; Omlor, Georg (Therapeutics and clinical risk management, 2018)
Initial peri- and postoperative antibiotic treatment of infected nonunions: results from 212 consecutive patients after mean follow-up of 34 months Lars Helbig,1 Maren Bechberger,2 Riyadh Aldeeri,1 Adriana Ivanova,1 Patrick Haubruck,1 Matthias Miska,1 Gerhard Schmidmaier,1 Georg W Omlor1 1Department of Orthopaedics, Trauma Surgery and Paraplegiology, 2Pharmacy Department, Heidelberg University Hospital, Heidelberg, Germany Purpose: Infected nonunions of the long bones belong to the most feared complications in the field of orthopedic and trauma surgery. Optimal antibiotic therapy should start early with the first revision surgery. Therefore, the aim of this study was to evaluate our peri- and postoperative antibiotic regime in context with the microbial spectrum and antibiotic resistances of patients with infected nonunions and to assess the possible impact on healing rates. Methods: We included all patients with first revision surgery during 2010–2015 due to nonunion of long bones with a clinical history of infection treated with radical debridement, local application of a gentamicin-impregnated bone cement, and systemic cefuroxime. Mean follow-up was 34.2 months. Data collection was performed retrospectively using a computerized databank with information about microbial species from intraoperatively acquired tissue samples and respective antibiograms. Bone fusion rates were evaluated based on findings of the latest X-rays and computed tomography scans.Results: Two hundred and twelve patients with nonunion and history of infection were selected; 171 patients had positive intraoperative microbial evidence of infection. Bacterial testing was mostly positive in fractures of the tibia (47.4%) and the femur (27.5%). Coagulase-negative Staphylococcus spp. were the most frequently detected (44.4%) followed by mixed infections (18.7%) and Staphylococcus aureus (10.5%). Antibiograms revealed that 62.6% of our cases were cefuroxime sensitive; 87.7% were gentamicin sensitive. Only 10.5% showed resistance to both cefuroxime and gentamicin. There was no statistically significant difference of fusion rates between patients with different microbial species or different antibiograms. Conclusion: Our data suggest that besides the high variety of different detected species, initial antibiotic treatment with a combination of systemic cefuroxime and local gentamicin-loaded bone cement is effective and in almost 90% the later determined microbial infection was sensitive to this treatment. Therefore, we recommend initial treatment according to this algorithm until specific antibiograms are available from intraoperatively acquired tissue samples. Keywords: infected nonunions, antibiotic treatment, microbial spectrum, antibiogram